Potassium homeostasis and therapeutic intervention with sodium zirconium cyclosilicate: A model‐informed drug development case study - Lindsay E. Clegg; Lulu Chu; Mats Nagard; David W. Boulton; Robert C. Penland (Wiley, 2024)
Abstract Potassium (K+) is the main intracellular cation in the body. Elevated K+ levels (hyperkalemia) increase the risk of life‐threatening arrhythmias and sudden cardiac death. However, the details of K+ homeostasis and the effects of orally administered K+ binders, such as sodium zirconium cyclosilicate (SZC), on K+ redistribution and excretion in patients remain incompletely understood. We built a fit‐for‐purpose systems pharmacology model to describe K+ homeostasis in hyperkalemic subjects and capture serum K+ (sK+) dynamics in response to acute and chronic administration of SZC. The resulting model describes K+ distribution in the gastrointestinal (GI) tract, blood, and extracellular and intracellular spaces of tissue, renal clearance of K+, and K+-SZC binding and excretion in the GI tract. The model, which was fit to time‐course sK+ data for individual patients from two clinical trials, accounts for bolus delivery of K+ in meals and oral doses of SZC. The virtual population of patients derived from fitting the model to these trials was then modified to predict the SZC dose-response and inform clinical trial design in two new applications: emergency lowering of sK+ in severe hyperkalemia and prevention of hyperkalemia between dialysis sessions in patients with end‐stage chronic kidney disease. In both cases, the model provided novel and useful insight that was borne out by the now completed clinical trials, providing a concrete case study of fit‐for‐purpose, model‐informed drug development after initial approval of a drug.